2010
DOI: 10.1111/j.1469-7610.2010.02262.x
|View full text |Cite
|
Sign up to set email alerts
|

Social and non‐social visual attention patterns and associative learning in infants at risk for autism

Abstract: Background Social inattention is common in children with autism whereas associative learning capabilities are considered a relative strength. Identifying early precursors of impairment associated with autism could lead to earlier identification of this disorder. The present study compared social and nonsocial visual attention patterns as well as associative learning in infant siblings of children with autism (AU sibs) and low risk (LR) infants at six months of age. Methods 25 AU sibs and 25 LR infants were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 40 publications
4
52
0
5
Order By: Relevance
“…The first finding is consistent with work indicating that during early development in children with ASD, social attention reduces while attention to exploration of objects increases (Bhat et al 2010;Koterba et al 2014). The second finding aligns with prior work demonstrating that, compared to TD peers, children with ASD responded to their mothers' approach behavior with more withdrawal behavior such as ignoring or shifting attention (Doussard-Roosevelt et al 2003), complied less with their mothers' instructions (Konstantareas and Stewart 2006), and displayed deficits in positive affect during joint attention activities (Kasari et al 1990).…”
Section: Emotional Content Of Coregulationsupporting
confidence: 80%
“…The first finding is consistent with work indicating that during early development in children with ASD, social attention reduces while attention to exploration of objects increases (Bhat et al 2010;Koterba et al 2014). The second finding aligns with prior work demonstrating that, compared to TD peers, children with ASD responded to their mothers' approach behavior with more withdrawal behavior such as ignoring or shifting attention (Doussard-Roosevelt et al 2003), complied less with their mothers' instructions (Konstantareas and Stewart 2006), and displayed deficits in positive affect during joint attention activities (Kasari et al 1990).…”
Section: Emotional Content Of Coregulationsupporting
confidence: 80%
“…However, it is important to note that in a number of these studies there was no longitudinal follow-up to determine whether the infants that performed poorly on these tasks would express BAP traits later in development (e.g. Bhat et al 2010;Goldberg et al 2005;Merin et al 2007;Nadig et al 2007;Presmanes et al 2007;Cassel et al 2007). Instead the infants examined in these studies may later display the full autism phenotype.…”
Section: Reciprocal Social Interactionmentioning
confidence: 95%
“…Siblings later classified as 'BAP+' also displayed deficits responding to joint attention compared to siblings later classified as 'BAP-' (Sullivan et al 2007). Other social behavioural deficits detected in at-risk siblings include reduced frequency of requesting behaviours (Goldberg et al 2005;Cassel et al 2007), reduced response to social interaction (Goldberg et al 2005) and differences in eye gaze movements; for example, shifting gaze to and from the caregiver less frequently (Ibanez et al 2008), gazing away from the caregiver for longer periods (Ibanez et al 2008), gazing less at the caregiver's eyes relative to the mouth (Merin et al 2007) and looking less at the caregiver and more at a novel object during a social-object learning task (Bhat et al 2010). However, it is important to note that in a number of these studies there was no longitudinal follow-up to determine whether the infants that performed poorly on these tasks would express BAP traits later in development (e.g.…”
Section: Reciprocal Social Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies evaluating the earliest signs of ASDs in siblings of children diagnosed with ASD suggest that while presentation is variable, siblings who develop ASD show signs of atypical development in language, social communication, and cognitive development, as well as sensory and motor functioning before the full clinical picture of autism develops (Zwaigenbaum et al 2009). Some studies have found differences in social functioning by the age of 6 months between younger siblings and controls (Bhat et al 2010), while others report that differences emerge by 12 months (Zwaigenbaum et al 2005). Whether these findings apply to singleton children or only to children with affected older sibs, and whether the behavioral manifestations will be observable in an office visit or common enough in affected infants to be useful for population screening have been unanswered questions.…”
Section: How Best To Screen?mentioning
confidence: 92%